2013
DOI: 10.1186/1756-0500-6-491
|View full text |Cite
|
Sign up to set email alerts
|

Identifying common and specific microRNAs expressed in peripheral blood mononuclear cell of type 1, type 2, and gestational diabetes mellitus patients

Abstract: BackgroundRegardless the regulatory function of microRNAs (miRNA), their differential expression pattern has been used to define miRNA signatures and to disclose disease biomarkers. To address the question of whether patients presenting the different types of diabetes mellitus could be distinguished on the basis of their miRNA and mRNA expression profiling, we obtained peripheral blood mononuclear cell (PBMC) RNAs from 7 type 1 (T1D), 7 type 2 (T2D), and 6 gestational diabetes (GDM) patients, which were hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 71 publications
4
103
1
2
Order By: Relevance
“…Many of these shared miRNAs have been associated with metabolic pathways, immunological processes, and tumorigenesis. Recent data confirmed that nine miRNAs were shared among the three types of diabetes, including hsa-miR-126, hsa-miR-144, hsa-miR-27a, hsa-miR-29b, hsa-miR-1307, hsa-miR-142-3p, hsa-miR-142-5p, hsa-miR-199a-5p, and hsa-miR-342-3p (Collares et al 2013). Thus, the aim of the study was to identify miRNAs whose activities changed in epicardial adipose tissue during hyperglycemia in piglets.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Many of these shared miRNAs have been associated with metabolic pathways, immunological processes, and tumorigenesis. Recent data confirmed that nine miRNAs were shared among the three types of diabetes, including hsa-miR-126, hsa-miR-144, hsa-miR-27a, hsa-miR-29b, hsa-miR-1307, hsa-miR-142-3p, hsa-miR-142-5p, hsa-miR-199a-5p, and hsa-miR-342-3p (Collares et al 2013). Thus, the aim of the study was to identify miRNAs whose activities changed in epicardial adipose tissue during hyperglycemia in piglets.…”
Section: Introductionmentioning
confidence: 89%
“…It has been proposed that peripheral blood mononuclear cells can be used as reporter cells to characterize the miR expression profiling during type 1 (T1D) and type 2 diabetes mellitus (T2D) and gestational diabetes mellitus. Collares and coworkers evaluated shared miRNAs among the major types of diabetes, including hsa-miR-29b, miR-142-3p, and hsa-miR-142-5p (Collares et al 2013). Many of these shared miRNAs have been associated with metabolic pathways, immunological processes, and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that there is a distinct pattern of circulating miRNAs in type 1 diabetes vs type 2 diabetes. Indeed, a study comparing miRNA profiles between type 1 diabetes, type 2 diabetes and GDM in peripheral blood mononuclear cells confirmed divergent profiles in the different forms of diabetes despite the fact that a few miRNAs are shared among the three groups [70].…”
Section: Current Limits To the Use Of Circulating Mirnas In Clinicalmentioning
confidence: 99%
“…Several studies have reported that acute physical activity and prolonged exercise training programmes can modify the circulating miRNA profile [87]. Furthermore, smoking appears to alter the pattern of circulating miRNAs [88][89][90][91], and of the miRNAs affected, miR-29b was identified to be deregulated in diabetic patients [27,28,70]. Environmental exposure to air pollutants and chemicals seems to modify circulating miRNAs [92], inducing a bias that is difficult to estimate.…”
Section: Current Limits To the Use Of Circulating Mirnas In Clinicalmentioning
confidence: 99%
See 1 more Smart Citation